The first-pass extraction of pindolol in comparison with propranolol in rat liver - Basset, Helen Margaret (Division of Clinical Pharmacology, 2018)
Reports in the literature have shown that in man propranolol has a larger first-pass effect (70%) than pindolol (13%). The aim of this research was to make a direct comparison of first-pass extraction and other pharmacokinetic parameters of these drugs under identical experimental conditions by means of an isolated rat liver perfusion model.